INOVASI “LOSSAVA” SEBAGAI BENTUK PEMANFAATAN PANGAN LOKAL SINGKONG DI SMP ISLAM AL-AZHAR CAIRO SUKOHARJO - Binardo Adi Seno Mawarno; Laela Nur Rokhmah; Jayanti Rahayu; Evida Agustina Sari (P3M Politeknik Negeri Malang, 2026)
The indicator of achievement in this community service activity is the creation of a high-value cassava product that is popular with the younger generation and has the potential to become an entrepreneurial product using simple equipment. The product produced is a long cassava stick called “Lossava,” inspired by a similar potato-based product widely sold in shopping malls. The activity was conducted through lectures and discussions on cassava as the primary raw material, followed by practical sessions on the production of “Lossava” and an evaluation phase, involves testing sensory characteristics, including taste, aroma, texture and overall acceptability of the products. The community service activity received a positive response from the students of SMP Al Azhar Cairo, who actively participated in the product creation process from raw material preparation, processing, to packaging, resulting in a new product not yet available in the market and favored by the participants. Going forward, it is hoped that the product innovation can be utilized as an entrepreneurial opportunity among teenagers, particularly at SMP Al-Azhar Cairo Sukoharjo, which also incorporates entrepreneurship education into its learning activities.